FORAGE PRODUCTION AND NUTRITIVE VALUE OF (Clitoria ternatea) HARVESTED AT 60, 75 AND 90 DAYS AFTER PLANTING - Jelantik, I G. N.; Nikolaus, T. T.; Leu Penu, C.; Malelak, Gemini E. M.; Benu, Imanuel (Pastura; Vol 8 No 2 (2019): Pastura Vol. 8 No. 2 Tahun 2019DO - 10.24843/Pastura.2019.v08.i02.p03, 2019)
The purpose of this experiment was to investigate herbage production and nutritive value of C. ternatea harvested at 60, 75 and 90 days after planting. The legume was planted in eighteen of 3 × 3 m2 plots a t 40 × 20 cm2. Forage was harvested at 60, 75 and 90 days after planting as treatmens. Variables measured included forage production, nutrient content and in vitro dry matter and organic matter digestibility. Herbage production was not significantly different (P>0.05) when harvested at different stages of growth. Leaf : stem ratio, however, declined (P<0.05) with advancing growth stage. Forage quality in terms of crude protein content was comparable (P>0.05) among different harvest time. Meanwhile the energetic value as shown by in vitro organic matter digestibility (IVOMD) was significantly higher (P<0.05) when C. ternatea was harvested 60 days compared to 75 and 90 days after planting. It can be concluded that for calf supplement, C. ternatea is preferably harvested at 60 d after planting. Key words : Clitoria ternatea, IVOMD, energy, calf supplement